Short shaft ratio: A novel predictor for dural ossification in patients with ossification of the ligamentum flavum - Jiabao Chen; Qingsong Yu; Haidong Wang; Huangda An; Chenhao Dou; Zhe Lu; Aoran Ding; Lei Ma (Heliyon, 2023)
Background: Dural ossification (DO) is strongly correlated with an increased incidence of complications during the surgery for the patients with thoracic ossification of the ligamentum flavum (OLF). Some methods for predicting DO have emerged, but the accuracy remains to be improved. We aimed to find a more accurate way to predict the appearance of DO. Methods: Retrospective study was adopted in this study. According to the intraoperative findings, ninety-one patients with thoracic OLF were ultimately included and divided into two groups based on the presence or absence of DO. Patient characteristics and radiographic data were recorded. The residual area ratio (RAR, residual area/cross-section area of normal spinal canal × 100%) and the short shaft ratio (SSR, the length of short shaft of the ellipse-like shape/the length of the spinal canal × 100%) were measured and calculated by 2 independent observers, followed by statistical analysis. The receiver operating characteristic curve was used to evaluate the accuracy of the SSR and RAR in predicting DO. Results: No significant differences were found in sex, age and BMI between the DO group and the non-DO group. The mean RAR (and standard deviation) in the Non-DO group (62.6% ± 10.2%) was significantly higher (p < 0.001) than that in the DO group (46.1% ± 10.5%). The mean SSR (and standard deviation) in the Non-DO group (61.6% ± 6.0%) was significantly higher (p < 0.001) than that in the DO group (43.6% ± 9.2%). The receiver operating characteristic curve indicated that the SSR and RAR can be used as the efficient indicators to identify DO, and the SSR has a higher accuracy in indicating the presence of DO, with a cutoff value of ＜48.71% (sensitivity of 100% and specificity of 85.0%). Conclusion: The SSR can be used as a supplement parameter to traditional methods to predict DO, and it could be a better predictor. And, compared with bilateral and bridged type, unilateral type of OLF was more likely to develop DO with a larger SSR.